The economics of the modern construction sector - Ive, Graham; Gruneberg, Stephen L. (Basingstoke : Macmillan, 2000)
This book will be of interest to built environment professionals and to students of the economics and management of the built environment. It shows the value of integrating ideas and data about the production of the built environment as an industrial process with theories and data about the demand for construction. The approach taken is institutional and post-Keynesian, and illuminates an important and distinctive sector of the economy, embracing design, construction and property industries. This book offers some new and important perspectives for research and teaching in construction economics and management.
Includes bibliographical references (P. 260-268) and index.
rpm 07/09/16
Loans
Keywords: Construction industry; Construction industry -- Mathematical models; Construction industry -- Economic aspects